Pelatihan Akuntansi Keuangan Daerah bagi Guru Akuntansi SMK Se-Kabupaten Mempawah - Mustafa, Bob; Kusmana, Endang; Ardhi, Qisthi; Dewi, V. Ananta Wikrama Tungga; Perdhiansyah, Perdhiansyah; Noor, Uray M.; Khamim, Khamim; Mahyus, Mahyus (Politeknik Negeri Pontianak, 2023)
This Community These Community Service Activities were initiated by the UPPM Team Accounting Department after coordinating with the Principal of SMKN 1 Mempawah Hilir in April 2022. The results of an initial survey via questionnaire of 8 accounting teachers in the Financial and Institutional Accounting Expertise Program showed that teachers still lack understanding of financial accounting area, as important material in learning Accounting Practicum for Government Agencies/institutions which focuses on recording transactions and completing the accounting cycle of Regional Work Units (SKPD). This is indicated by the fact that most of the accounting teachers in the Institutional Accounting and Finance Expertise Program do not understand the types of source documents for recording transactions and techniques for recording transactions, as well as completing the SKPD accounting cycle. The solution offered by the UPPM Team of the Accounting Department to solve partner problems is to organize Regional Financial Accounting Training for Accounting Teachers at Vocational Schools throughout Mempawah Regency. The target of this activity is that 12 teachers who teach in the Institutional Accounting and Financial Expertise Program in Mempawah Regency can record transactions and complete SKPD accounting cycles, making it easier for teachers to teach every material in the Accounting Practicum subject for Government Agencies/Institutions to students in their schools. each. This training will be held on Monday, October 3, 2022 in the Lab Room. Computer SMK Negeri 1 Mempawah Hilir. This training was attended by 12 accounting teachers from SMK Negeri 1 Mempawah Hilir and SMK Negeri Sungai Kunyit. Activities run smoothly from 08.30 – 16.00 WIB. After attending the training, there was a significant difference in the level of understanding of the participants compared to before attending the training. Participants' knowledge of regional financial accounting increased, as well as skills in carrying out the practice of preparing SKPD financial reports. This shows that the training was carried out effectively. Hopefully the results of this training activity will be useful for teachers in transferring knowledge to their students in the Accounting Practicum subject for Government Agencies/Institutions in their respective schools. Before the event was closed, the PPM Team of the Polnep Accounting Department handed over 12 textbooks to the participants. The session of presenting souvenirs to the Principal of SMK Negeri 1 Mempawah Hilir and taking a group photo ended this activity.